Dewetting dynamics of metal/metallic coated ceramic systems at high temperatures - Ran Sui; Qiaoli Lin (Applied Surface Science Advances)
This work focuses on kinetic analysis of high-temperature dewetting at metal/ceramic interfaces. Metal films were deposited on ceramics via magnetron sputtering, followed by wetting tests with tin, aluminum, and copper droplets. Results revealed asymmetric wetting-dewetting, indicating strong chemical bonds instead of reversible physical ones at high temperatures, deviating from traditional model predictions. Current room-temperature dewetting models (including hydrodynamic model, molecular kinetic theory and the combined model) fail to accurately describe high-temperature dewetting dynamics on metallized ceramics. Dewetting is governed by the metal film diffusion in droplets or the decomposition reaction kinetic at triple line, seen in diffusion-limited model in Sn/Ag-Ti on ZrO2 and Sn/FeCoNiCrCu coated h-BN, and decomposition reaction model in Cu/FeCoNiCrCu on sapphire. These insights are crucial for designing stable high-temperature metallurgical interfaces.